1993
DOI: 10.1073/pnas.90.18.8653
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme crystal structure in a neat organic solvent.

Abstract: The crystal structure of the serine protease subtllsln Carbsberg In anhydrous acetonitrile was determined at 2.3 A rolution. It was found to be easentially Identical to the tbree-dimensional structure of the enzyme In water; the differences observed were smaller than those between two lndependentiy determined struchre In aqueous solution. The hydrogen bond system of the catalytic triad is intact in acetonitrile. The majority (99 of 119) of enzyme-bound, structural water molcules have such a great affnity to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
146
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(153 citation statements)
references
References 27 publications
6
146
0
1
Order By: Relevance
“…Previously, we solved the x-ray crystal structures of lightly crosslinked subtilisin Carlsberg in dioxane (17), acetonitrile (15), and water (16) and found them virtually identical, with an rmsd of the backbone atoms of 0.3 Å among the different structures. However, to determine whether the enzyme mechanism is the same in organic solvent as in water, one must examine the structure of a reaction intermediate formed in both media, not just the structure of the free enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we solved the x-ray crystal structures of lightly crosslinked subtilisin Carlsberg in dioxane (17), acetonitrile (15), and water (16) and found them virtually identical, with an rmsd of the backbone atoms of 0.3 Å among the different structures. However, to determine whether the enzyme mechanism is the same in organic solvent as in water, one must examine the structure of a reaction intermediate formed in both media, not just the structure of the free enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…Rigid body refinement (10-4.0 Å) was performed using X-PLOR (29) for acetonitrile and water data and coordinates for the corresponding cross-linked nonacylated crystal structure PDB 1scb and 1sca (15,16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The result obtained from MD simulation of WT TLL in methanol is consistent with a previous circular dichroism spectra study of WT TLL in high concentration isopropanol solutions (up to 50%), which revealed that isopropanol molecules did not cause major alterations in secondary structure, although the enzyme became completely inactive in 50% isopropanol [34]. X-ray structures of serine proteases, subtilisin Carlsberg and porcine pancreatic elastase, crystallized in neat acetonitrile, 80% (v/v) isopropanol and 80% (v/v) ethanol, respectively, also confirmed a native-like secondary structure of each enzyme [35] and [14].…”
Section: The Overall Conformational Changes Induced By Methanolmentioning
confidence: 76%